EFFECT OF ROBUSTA COFFEE BEANS AND ARABICA EXTRACT GEL AS INFLAMATION PULP MATERIAL - Sherli Diana; Nadiya Amalia; Deby Kania Tri Putri (Dentino : Jurnal Kedokteran Gigi, 2023)
Background: Reversible pulpitis is a mild to moderate inflammatory pulp condition often treated with pulp capping treatments. Current study states that calcium hydroxide (CaOH2) has drawbacks for a long-time use. One of the alternative pulp capping materials is Robusta and Arabica coffee bean extract gel which contains flavonoid compounds and chlorogenic acid which have immunomodulatory properties that play role in the pulp inflammatory process by increasing the count of lymphocyte. Objective: The goal of this study is to determine and analyse the effect of Robusta coffee bean and Arabica coffee bean extract gel 95% to the of lymphocyte cells count on the 3rd and 5th day of pulp inflammation compared to placebo gel. Materials and Methods: This research is a true experimental with a post-test only control group design. This study used three treatment groups; Robusta coffee bean extract gel 95%, Arabica coffee bean extract  gel 95%, and control group placebo gel. Results: Two Way Anova test results obtained p<0.05, showed significant difference. Data analysis was continued with the Post Hoc Bonferroni test which showed that there was a significant difference between the 95% Robusta coffee bean extract gel group and the 95% Arabica coffee bean extract gel group with p<0.05. Conclusion: The administration of Robusta coffee bean extract gel with a concentration of 95% can increase the of lymphocyte cells count in pulp inflammation on the 3rd and 5th days more effectively than the 95% Arabica coffee bean extract gel. Keywords: Arabica Coffee, Direct Pulp Capping, Inflammation, Lymphocytes, Pulpitis, Robusta Coffee